Understanding augmented reality : concepts and applications - Craig, Alan B. (Elsevier, Morgan Kaufmann, 2013)
"Chapter 1 introduces the idea that augmented reality (AR) is a medium. Although it is a medium, there is technology that is required to carry it out. In much the same way that technology is required for other media, like movies, AR also utilizes technology to carry out the ideas represented in the medium. It is important to learn about the medium first and foremost and then the technology. A movie producer must understand the medium and its affordances, how it can be used to tell a story, etc. in order to create a compelling movie. Simply learning about cameras and projectors does not enable one to make great movies. The same is true with augmented reality. Simply learning about the technology does not enable an AR producer to create compelling AR applications. Chapter 1 also provides a history of augmented reality, compares and situates augmented reality with related media an technologies, and defines some key terms related to augmented reality, including the definition for augmented reality that is used throughout the book"--Resumé vydavatele
Obsahuje rejstřík
Keywords: rozšířená realita; augmented reality; příručky; elektronické knihy; handbooks and manuals; electronic books